KEMAMPUAN MANAJERIAL KYAI DALAM MENGELOLA PONDOK PESANTREN AL-ITTIFAQ - Sri Widaningsih (JURNAL KEPEMIMPINAN DAN PENGURUSAN SEKOLAH, 2023)
The important meaning of management  implementation of  the boarding school is very helpful for the achievement of educational goals. This study aims to portray and analyze the managerial skills of a Kyai in  process to manage a  boarding school. This study uses qualitative methods with a "naturalistic phenomenological" approach adopted from Bogdan and Biklen (1982). Such an approach puts researchers operationally as the main instrument which came to a data source directly. Data collected through observation, interview and documentation. The data presented in words and analyzed  through inductive analysis to reveal the meaning of the condition that has been observed. This study seeks to describe what it is about the managerial ability of a Kyai in the management of Boarding Schools. The impact can help to improve the value and the quality of boarding school itself. The results of this research will reveal about (1) managerial concepts that are being implemented now, (2) design that is  suitable for the development of managerial boarding school, and (3) The impact of managerial design in order to improve the value and the quality of Al-Ittifaq boarding school. Based on the findings in the field and referrals from existing theory then all of them almost 100% concept that has been done by Kyai in the process of management of boarding school is almost the same as the existing theory, just need the full adjustment of the concepts and theories of management that existing and developing these days , and the most important thing is all must be surely supported by all components of education at boarding school. Therefore, researchers recomend to all parties concerned with general education, especially education at the cottage boarding to be able to add insight into the management concepts deeply, particularly on the concept of the managerial ability of educational institutions boarding school, because targeted and systematically structured management  in management process can help to reach the goal.